Electric lighting - Thompson, George Kirk (My University, 1893)
Introduction: Scientists are generally agreed that there has been in each period of the world’s history, certain predominating features, which have eminently characterized each period from all others. The same general statement, might with due propriety, be made as regards the intellectual development of the world. With each advancing step there has been a thought, a movement, a work accomplished, that has stood a living monument to all future time and we who are blessed with the rich heritage of all that has proceeded, are now to be immortalized by a period of growth that will be known to all posterity, as the “Age of Electricity.”
Citation: Thompson, George Kirk. Electric lighting. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: World history; Intellectual development; Age of electricity; Theses; Manuscripts (documents)